Shear Strength of Brackets Bonded with Universal Adhesive Containing 10-MDP after 20,000 Thermal Cycles - Mariana Almeida Mello Proença; Karime Tavares Lima da Silva; Alisson Costa e Silva; Edilausson Moreno Carvalho; José Bauer; Ceci Nunes Carvalho (International Journal of Dentistry)
Objectives. The aim of this study was to evaluate the shear bond strength of metal brackets bonded with different universal adhesive systems containing 10-MDP and Transbond Plus Self Etching Primer after 20,000 thermal cycles. Materials and Methods. A total of 130 sound bovine teeth were used, which are divided into 5 groups (n = 26) according to the adhesive system used: All-Bond Universal (Bisco), Ambar Universal (FGM), Clearfil Universal Bond (Kuraray), Single Bond Universal (3M/ESPE), and Transbond Plus SEP (3M/ESPE) as control. The adhesives were applied for 20 seconds and bonded with a resin Transbond XT (3M/ESPE). After this, the teeth were submitted to 20,000 cycles at 5°C and 55°C. Afterwards, the shear bond strength test was performed in a universal test machine (Instron 3342). The adhesive remnant index (ARI) was evaluated under a stereomicroscope at 10x magnification and scanning electronic microscopy (SEM, Hitachi 3030). The shear bond strength data were submitted to One-Way ANOVA (α = 0.05) and the ARI to the Kruskal–Wallis test (α = 0.05). Results. Statistical analysis showed that the universal adhesive systems presented mean shear bond strength values similar to Transbond Plus SEP (p<0.05). The universal adhesive presented similar ARI values among them but differed from those of Transbond Plus SEP (p<0.001). Transbond Plus SEP presented a high ARI value when compared with the universal adhesive systems and high demineralization of enamel. Conclusions. The results show that universal adhesive systems may be used for bonding metal brackets if the orthodontist wants to maintain dental enamel health.